HOW IS THE ESG FACTOR RELATED TO TRADITIONAL FACTORS? : - Ngo, Tam Thi (2020)
This master thesis discusses ESG effect on the portfolio performance and how this factor is relatedto conventional factors. First, ESG-related portfolios and the ESG factor portfolio are constructedbased on ESG score. Second, return, standard deviation and Sharpe ratio are calculated to presentportfolio performance. Finally, 12 asset pricing models are run on the portfolio and single-stockslevel. ESG factor is added into base models. We observe that the higher ESG-scored portfolio doesnot lead to the better return compared to the lower ESG-scored portfolio. The analysis of assetpricing models on the portfolio level shows that the ESG factor does not enhance the explanatorypower of traditional models. The analysis on single stocks illustrates that ESG factor can explainexpected return better higher than CMA only, but worse than MKT, SMB+HML, WML, RMWand RMW+CMA.